Scoping Review: Profil Pengobatan Pasien Stroke Iskemik Di Indonesia Setelah Dikeluarkannya Panduan Nasional Pelayanan Kedokteran Stroke Tahun 2019: Scoping Review: The Drug Therapy Profile of Ischemic Stroke Patients in Indonesia Following of the 2019 National Guidelines for Stroke Medical Service - Lisnawati, Retno; Panduwiguna, Ivans; Saepudin (Media Farmasi, 2025)
In Indonesia, stroke is one of the leading causes of morbidity and mortality. The National Guidelines for Medical Services Stroke (PNPK) which was established in 2019, provides guidance for raising the bar for stroke treatment. The purpose of this scoping study is to understand the profile of stroke patients in Indonesia following the PNPK 2019 with an emphasis on drug therapy, evaluation, and rationality. This study used a scoping review design with article searches using the PubMed and Google Scholar databases from 2020 to 2024. Criteria for inclusion include articles about stroke prevention in Indonesia, which can be accessed and used after PNPK 2019. From 1288 articles in PubMed and 80 articles in Google Scholar, 11 articles were selected that met the criteria. The most commonly used treatment combinations for stroke patients are neuroprotectants, antiplatelet, antihypertensive, and anti dislipidemia. Neuroprotectants, such as Citicoline, are the most commonly used drugs. The most effective antihypertensive treatment is a combination of CCB and ARBs. The majority of articles demonstrate high drug rationality, with accurate indication, patient, medication, and dosage reaching 100%. There are advantages to using rtPA for thrombolysis treatment, particularly in terms of onset time, access, and systemic benefits. While the profile of drug therapy among ischemic stroke patients in Indonesia demonstrates high rationality, the 2019 PNPK Stroke places more emphasis on therapy for ischemic stroke patients in the hyperacute phase, However, research on the application of therapy in hyperacute phase ischemic stroke patients has not been extensively conducted.